Functional Characterization of Soybean Diacylglycerol Acyltransferase 3 in Yeast and Soybean - Xue, Jinai; Gao, Huiling; Xue, Yinghong; Shi, Ruixiang; Liu, Mengmeng; Han, Lijun; Gao, Yu; Zhou, Yali; Zhang, Fei; Zhang, Haiping; Jia, Xiaoyun; Li, Runzhi (Frontiers in Plant Science, 2022)
Diacylglycerol acyltransferases (DGAT) function as the key rate-limiting enzymes in de novo biosynthesis of triacylglycerol (TAG) by transferring an acyl group from acyl-CoA to sn-3 of diacylglycerol (DAG) to form TAG. Here, two members of type 3 DGAT gene family, GmDGAT3-1 and GmDGAT3-2, were identified from soybean (Glycine max) genome. Both of them were predicted to encode soluble cytosolic proteins containing the typical thioredoxin-like ferredoxin domain. Quantitative PCR analysis revealed that GmDGAT3-2 expression was much higher than GmDGAT3-1’s in various soybean tissues such as leaves, flowers and seeds. Functional complementation assay using TAG-deficient yeast (Saccharomyces cerevisiae) mutant H1246 demonstrated that GmDGAT3-2 fully restored TAG biosynthesis in the yeast and preferentially incorporated monounsaturated fatty acids (MUFAs), especially oleic acid (C18:1) into TAGs. This substrate specificity was further verified by fatty-acid feeding assays and in vitro enzyme activity characterization. Notably, transgenic tobacco (Nicotiana benthamiana) data showed that heterogeneous expression of GmDGAT3-2 resulted in significant increase of seed oil and C18:1 levels, but little change in contents of protein and starch compared to the EV-transformed tobacco plants. Taken together, GmDGAT3-2 displayed a strong enzymatic activity to catalyze TAG assembly with high substrate specificity for MUFAs, particularly C18:1, playing an important role in the cytosolic pathway of TAG synthesis in soybean. The present findings provide a scientific reference for improving oil yield and FA composition in soybean through gene modification, further expanding our knowledge of TAG biosynthesis and its regulatory mechanism in oilseeds.